Genetic recombination in Nocardia asteroides. - Kasweck, K L (1982)
Gene recombination between strains of Nocardia asteroides of diverse origins has been demonstrated. In particular pairwise combinations, recombinants made up 0.01% of the population. All nine selectable recombinant classes were recovered from a cross KK4-47 his-10 leu-1 and KK6-119 met-3 phe-3. Recombinants with an auxotrophic marker from each parent constitute 21% of the recombinants.